Champagne: marketplace icon. Issue 3 (4th May 2017) - Rokka, Joonas
ABSTRACT: What makes a simple wine, grown in a rather mediocre wine-growing region, one of the most famous and magical marketplace icons of today? How did champagne establish such a unique position, against all the odds, and become the global symbol of celebration? In seeking answers to these questions, this marketplace icon contribution elaborates on what 250 years of avant-garde champagne marketing can tell us about champagne's ever-shifting image and role in consumer culture. I argue that the "imperishable fame" of champagne stems primarily from four epic myth-making moments that not only came to shape a national identity but also modern consumption ideologies in important ways.